2019
DOI: 10.1021/acs.jpcc.9b09604
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Two Distinct Peaks of Ice in the THz Region and Its Application for Natural Gas Hydrate Dissociation

Abstract: For liquid water in the far-infrared spectrum, phonons of molecular vibrations constitute two bands with a narrow gap at around 30 meV. Interestingly, there are two distinct peaks for ice in this gap. We demonstrated that the two peaks come from two kinds of translational modes. Considering different O–O–O bending constants, we yielded two frequencies based on the ideal model of ice Ic. These two kinds of vibrational modes do not exist in liquid water due to the collapse of the rigid tetrahedral structure. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 44 publications
4
25
0
2
Order By: Relevance
“…We first found the two kinds of intrinsic HB vibrational modes in H-ordered ice Ic, which has only two molecules per primitive cell [21]. Then, we confirmed that the two distinct HB peaks in ice Ih originated from these two kinds of HB modes [19]. By now, we have investigated almost all the ice phases, thereby determining that this is a general rule for ice because of its local tetrahedral structure [18].…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…We first found the two kinds of intrinsic HB vibrational modes in H-ordered ice Ic, which has only two molecules per primitive cell [21]. Then, we confirmed that the two distinct HB peaks in ice Ih originated from these two kinds of HB modes [19]. By now, we have investigated almost all the ice phases, thereby determining that this is a general rule for ice because of its local tetrahedral structure [18].…”
Section: Discussionsupporting
confidence: 51%
“…To determine the two kinds of HB vibrational modes in ice III, we employed a selfcompiled program to classify the normal modes in the translation band [19]. The criterion for classification is based on the included angle between the vibrational direction and the H-O-H angle bisector.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vibrational frequency of the two-bond mode is weaker than that of the four-bond mode. The dynamic processes of these modes are described in refs and .…”
Section: Results and Discussionmentioning
confidence: 99%